Investigation of Some Methods for Estimating the Mutual Dynamic Stability of Stochastic Processes - S. A. Pyko; N. S. Pyko; O. A. Markelov; Y. D. Uljanitski; M. I. Bogachev (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The sensitivity of some methods for estimating the mutual dynamic stability of stochastic processes with given correlative properties was studied in relation to the phase detuning between the processes. Two classes of normally distributed random stochastic processes are considered: the processes with short-term correlation and the processes with a long-term correlation, characterized by the specified Hurst coefficients.